2018
DOI: 10.1108/jcre-04-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of physical office environments for employee outcomes

Abstract: Purpose This study aims at understanding academic practice in the field of physical office environment research and providing recommendations for further enhancement of the field. It shows which effects of the physical office environment on employee outcomes are studied by which disciplines, and which methodologies are used by whom and on which variables. Existing gaps in research that are confirmed by these analyses are discussed and “assigned” to obvious, best suited combinations of future multi-disciplinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 39 publications
3
44
0
Order By: Relevance
“…The importance of spatial design was emphasized by many researchers [28][29][30]32], but it is observed that individual space and IEQ factor "Personal control" are becoming the occupant's priority in a well-designed office. The recent studies on open-plan offices have highlighted the importance of individual space and personal control as having significant and positive impact on perceived productivity [12,21].…”
Section: Perceived Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of spatial design was emphasized by many researchers [28][29][30]32], but it is observed that individual space and IEQ factor "Personal control" are becoming the occupant's priority in a well-designed office. The recent studies on open-plan offices have highlighted the importance of individual space and personal control as having significant and positive impact on perceived productivity [12,21].…”
Section: Perceived Productivitymentioning
confidence: 99%
“…Despite these benefits, there is a growing body of research and anecdotal evidence from industry pointing to several issues related to poor indoor environmental quality (IEQ) performance and its negative impacts on office workers [7][8][9][10]. IEQ has been proven to negatively affect occupants [11,12]. In order to get rid of the problem of measuring productivity caused by varied outputs from office occupiers, most of the researchers have done productivity studies based on self-assessment questionnaires with a subjective rating [13].…”
Section: Introductionmentioning
confidence: 99%
“…Even if the decision of using coworking spaces is done by the management of a company, the extent to which coworking space benefits suit end-users heavily relies on their expectations and preferences. The workplace support of end-users influences several organizational outcomes such as productivity and collaboration (Appel-Meulenbroek et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the workforce and workplace is complex and highly dynamic where there has been very little research that examines specifically the impact of the physical space on the individual knowledge worker [2]. Researchers have undertaken Dephi [3] and PRISMA lead research [4] analysing hundreds of existing related publications, papers and industry reports to digest down to critical thematic narratives and conclusions. The same study [4] established that the focus for assessing workplace productivity and worker efficiency came from researchers in the fields of psychology 34%, architecture 33%, management 10%, real estate 8%, engineering 7%, building physics 8%, health 4%.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have undertaken Dephi [3] and PRISMA lead research [4] analysing hundreds of existing related publications, papers and industry reports to digest down to critical thematic narratives and conclusions. The same study [4] established that the focus for assessing workplace productivity and worker efficiency came from researchers in the fields of psychology 34%, architecture 33%, management 10%, real estate 8%, engineering 7%, building physics 8%, health 4%. Additionally, other systematic research reviews [2] find there are a gap and lack of research on productivity measurement in the knowledge worker areas certainly over the last ten years with a focus mainly on technology in the workplace with little in-depth analysis flowing out of initial studies [5].…”
Section: Introductionmentioning
confidence: 99%